The South African Communist Party adapting to thrive in a post-communist age - Kolasa, Thomas Stanley 1967- (McFarland & Company, Inc., Publishers, 2015)
"This history describes how the South African Communist Party has flourished in a harsh political environment. Formed in 1921 as an affiliation of leftist organizations, it fought against the racist Apartheid regime, ascending to power in 1994 with the African National Congress. SACP is working towards a socialist future for South Africa while governing a capitalist country"...